Vascular Normalization: A New Window Opened for Cancer Therapies - Yang, Ting; Xiao, Hongqi; Liu, Xiaoxia; Wang, Zhihui; Zhang, Qingbai; Wei, Nianjin; Guo, Xinggang (Frontiers in Oncology, 2021)
Preclinical and clinical antiangiogenic approaches, with such multiple side effects as resistance, have not been proved to be very successful in treating tumor blood vessels which are important targets for tumor therapy. Meanwhile, restoring aberrant tumor blood vessels, known as tumor vascular normalization, has been shown not only capable of reducing tumor invasion and metastasis, but also of enhancing the effectiveness of chemotherapy, radiation therapy and immunotherapy. In addition to the introduction of such methods of promoting tumor vascular normalization as maintaining the balance between proangiogenic and antiangiogenic factors, targeting endothelial cell metabolism, microRNAs, extracellular matrix, the latest molecular mechanisms and the potential connections between them were primarily explored. In particular, the immuno treatment-induced normalization of blood vessels further promotes infiltration of immune effector cells, which in turn improves immunotherapy, thus forming an enhanced loop. Thus immunotherapy in combination with antiangiogenic agentsthe is recommended. Finally, we introduce the imaging technologies and serum markers, which can be used to determine the window for tumor vascular normalization.